Revenue Recognition Evaluation in Construction Companies - Parso, Parso; Mansur, Mansur (Jurnal Multidisiplin Sahombu, 2025)
This study evaluates the application of PSAK 72 in revenue recognition at PT. ABC, a construction company. PSAK 72, which replaces PSAK 23 and PSAK 34, introduces a principle-based approach that requires revenue to be recognized upon fulfilling contractual obligations. The research examines whether PT. ABC’s revenue recognition process aligns with PSAK 72’s five-step framework, including contract identification, combination, modification, performance obligation identification, and fulfillment. The study adopts a qualitative approach, utilizing interviews, financial reports, and contract analysis. Findings indicate that PT. ABC largely complies with PSAK 72, particularly in contract identification, combination, modification, and fulfillment of performance obligations. However, the company has not fully implemented the identification of distinct performance obligations. Revenue recognition is conducted progressively based on project completion, using the percentage-of-completion method. The study highlights challenges in aligning construction contracts with PSAK 72, particularly in distinguishing separate obligations within a single contract. The research emphasizes the need for increased awareness and training on PSAK 72 to ensure full compliance. The findings contribute to understanding revenue recognition in the construction industry and suggest further research on PSAK 72 implementation across different sectors.